A Web Site to Improve Management of Patients with Inherited Bleeding Disorders in the Emergency Department: Results at 2 Years - Tagliaferri, Annarita; Di Perna, Caterina; Biasoli, Chiara; Rivolta, Gianna Franca; Quintavalle, Gabriele; Cervellin, Gianfranco; Barozzi, Marco; Benedettini, Laura; Pattacini, Corrado; for the Haemophilia Centres and Emergency Department Network of the Region of Emilia-Romagna (Seminars in Thrombosis and Hemostasis, 2016)
Treatment of patients with inherited bleeding disorders (PWIBD) in the emergency department (ED) is challenging. In 2010, a project was started involving all eight hemophilia centers (HC) and all 44 EDs of the Region of Emilia-Romagna (Italy) to improve emergency care for PWIBD. The project incorporates guidelines for emergency treatment, education for ED staff, and a dedicated Web site providing extensive information, proposing treatments, and sharing data with patients' electronic clinical records. A Web algorithm, accessible to PWIBD as well as ED and HC staff, suggests the first dose of concentrate for each type and severity of bleed or trauma. Following training courses in each ED, the network was activated. During 2012 and 2013, the site was visited 14,000 times, the EDs accessed the Web site 1,739 times, and used the algorithms 206 times. In two reference EDs, triage-assessment and triage-treatment times were reduced in 2013 and 2012 (27/20 and 110/71.5 minutes, respectively) and medical advice from the HC increased (54 vs. 24% cases). The main advantages of this system are better management of patients in ED (shorter triage-to-treatment times) and improved collaboration between HCs and EDs. The most critical point remaining is staff turnover in EDs, necessitating continual training.
Keywords: inherited bleeding disorders; emergency care; Web site; therapeutic algorithm